A CINEMATIC MUSEUM OF MEMORY: MONUMENTS OF DEIMANTAS NARKEVIČIUS - BERTAŠAVIČIŪTĖ, RIMA (Politologija, 2013)
The paper aims at describing the problem of historical memory such as it emerges in the films of the contemporary Lithuanian video-artist Deimantas Narkevičius. The questions raised are whether it may be conveyed through cinematic means and which techniques in particular may well preserve and nourish it. In the oeuvre of Narkevičius, the problem is closely tied to the autoreflexivity of the medium itself, since cinema allows recalling events both personal and “universal” and moving them from one context to another, forcing them to lose their documental status in the process. Yet no manipulation of document and history may pass without consequences, and all historic images, traumatic narratives and translating between different languages and experiences reveal ruptures in the narrative texture. This, in turn, makes us question the possibility and probability of memory itself. These questions are in the forth of Narkevičius’ films, yet they are posed wordlessly, through images alone, thus making the spectator wonder as to whether cinema might have its own techniques of working with the memory, history, and forgetting. Editing is the main cinematic technique used in the process, and the “Role of a Lifetime” of Narkevičius, to quote his another film, proves to be one of the Great Editor. Editing empowers one with the means of control over cinematic discourse and thus provides a very particular type of cinematic memory. Instead of merely showing things, the editor has control over what shall and shall not be seen. Yet Narkevičius chooses not to merely tell documentary stories about a life long gone. Instead, he reviews the once-traditional ways of looking (soviet filming techniques, film and TV genres) aiming at revealing their own inner instability, forcing them to display their own ruptures and discontinuities. A strategy like that closely resembles such practices of the Soviet Lithuanian art as the so-called “Quiet Modernism” or “Aesop’s language”; yet the overall status of Narkevičius’ work is under the question. Is such a strategy merely a suggestion of a way of remembering? Or, is it a convenient and institutionally approved way of opposing the mainstream? The films analysed here provide no definite answer; however, they do prove that the means of the medium play a significant role in how we perceive and understand our past.